Efficacy and safety of disinfectants for decontamination of N95 and sn95 filtering facepiece respirators: a Systematic review (2020)
Background: Decontaminating and re-using filtering facepiece respirators (FFRs) for healthcare workers is a potential solution to address inadequate FFR supply during a global pandemic. Aim: The objective of this review was to synthesize existing data on the effectiveness and safety of using chemical disinfectants to decontaminate N95 FFRs. Methods: We conducted a systematic review on disinfectants to decontaminate N95 FFRs using Embase, Medline, Global Health, Google Scholar, WHO feed, and MedRxiv. Two reviewers independently determined study eligibility and extracted predefined data fields. Original research reporting on N95 FFR function, decontamination, safety, or FFR fit following decontamination with a disinfectant was included. Findings and Conclusions: A single cycle of vaporized hydrogen peroxide (H2O2) successfully removes viral pathogens without affecting airflow resistance or fit, and maintains an initial filter penetration of <5%, with little change in FFR appearance. Residual hydrogen peroxide levels following decontamination were within safe limits. More than one decontamination cycle of vaporized H2O2 may be possible but further information is required on how multiple cycles would affect FFR fit in a real world setting before the upper limit can be established. Although immersion in liquid H2O2 does not appear to adversely affect FFR function, there is no available data on its ability to remove infectious pathogens from FFRs or its impact on FFR fit. Sodium hypochlorite, ethanol, isopropyl alcohol and ethylene oxide are not recommended due to safety concerns or negative effects on FFR function.